2006
DOI: 10.1002/ijc.21727
|View full text |Cite
|
Sign up to set email alerts
|

The Salzburg concept of intraoperative radiotherapy for breast cancer: Results and considerations

Abstract: Aim of this study is to show that ipsilateral breast tumor recurrence (IBTR) after breast conserving surgery can be reduced by proper surgery and modern radiotherapy techniques. Three hundred and seventy eight women with stage I or II breast cancer had breast conserving surgery and received 51-56.1 Gy of postoperative radiation to the whole breast in 1.7 Gy fractions, but patients received different boost strategies. Group 1 (n 5 188) received electron boost radiation of 12 Gy subsequent to the irradiation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 40 publications
(47 reference statements)
2
35
0
2
Order By: Relevance
“…Furthermore, in a retrospective matched-pair analysis, 188 patients with external electron boost (6 × 2 Gy) were compared to 190 IOERT patients from the Salzburg cohort [24]. At 5-year follow up, the in-breast recurrence rate in the external electron boost group was 4.3% compared to 0% in the IOERT group.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Furthermore, in a retrospective matched-pair analysis, 188 patients with external electron boost (6 × 2 Gy) were compared to 190 IOERT patients from the Salzburg cohort [24]. At 5-year follow up, the in-breast recurrence rate in the external electron boost group was 4.3% compared to 0% in the IOERT group.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…With regard to another concept of full-dose intraoperative radiotherapy, an anticipated boost during operation has been studied (Reitsamer et al, 2002;Reitsamer et al, 2006). A single dose of 9 Gy was applied to the 90% reference isodose with energies ranging from 4 to 15 MeV, using round applicator tubes 4-8 cm in diameter.…”
Section: As a Boostmentioning
confidence: 99%
“…The advantages are follows. 1) To complete skin sparing, 2) the precise application of the boost directly to the tumor bed with a homogeneous tissue radiation and 3) to reduce postoperative radiation time for 7-10 days (time of postoperative boost radiotherapy) (Reitsamer, et al, 2002;Reitsamer, et al, 2006).…”
Section: As a Boostmentioning
confidence: 99%
“…4 European trials initiating partial breast irradiation before 1990 showed an annual local recurrence rate of up to 10%, while more recent series have demonstrated an annual local recurrence rate below 1% [31]. The Fitzal/Riedl/Jakesz Salzburg trial showed improved local recurrence rates in partial breast-irradiated patients compared with whole breast-irradiated patients [32]. Patients in the trials differed in terms of grading, tumour size and age, which may have contributed to the better results in the later trials.…”
Section: Partial Breast Irradiationmentioning
confidence: 99%